(untitled) (Asian Journal of Applied Sciences, 2014)
The status of the marine artisanal fishery in the northwest Arabian Gulf was evaluated for the period 1965 to 2011. The data for total and species landings and fishing effort were collected from the landings site in Al-Fao port, Iraq during 2007- 2011, and compared with historical fishing information for the period 1965-2006. Annual total landings fluctuated from 582 t in 1965 to 22901 t in 2002. The monthly trend of the total catches followed the variations in landings for river shad, Tenuolosa ilisha and mullet species. The contributions of river shad to total landings declined gradually from 90.2% (1965-1973), 52.9% (1991-1994), 41.8% (1995-1999), 30.7% (2000-2006) and 18.9% (2007-2011). The number of fishing boats decreased significantly during 2011 compared to that during the late 1990s. There are several reasons that may have contributed to the decline in marine fish landings over recent years, such as large reduction in the discharge rates of the Shatt Al-Arab River, over-fishing of key species and no regulations to protect and manage marine resources.